2020
DOI: 10.1002/vnl.21766
|View full text |Cite
|
Sign up to set email alerts
|

Strength Improvement of Additive Manufacturing Components by Reinforcing Carbon Fiber and by Employing Bioinspired Interlock Sutures

Abstract: The additive manufacturing (AM) process is used to build three‐dimensional (3D)‐printed components by depositing layers of materials one over another until it completes the building process. There are numerous ways to improve its strength and rigidity of AM processed components. In this research, we discuss an effective method to improve the strength of 3D‐printed component joints by reinforcing carbon fiber (CF) with polylactic acid (PLA) and applying bioinspired interlock sutures. The strength of 3D‐printed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…For instance, it was observed that the infill density and layer thickness have significantly influenced the tensile strength of ABS polymer 16 . High infill density gives high tensile strength and good surface characteristics for PETG material 17 . Apart from changes in internal process parameters, some external changes were also considered to obtain the expected mechanical performance of printed material by adding carbon fibers (short/lengthy) along with polymers 18 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was observed that the infill density and layer thickness have significantly influenced the tensile strength of ABS polymer 16 . High infill density gives high tensile strength and good surface characteristics for PETG material 17 . Apart from changes in internal process parameters, some external changes were also considered to obtain the expected mechanical performance of printed material by adding carbon fibers (short/lengthy) along with polymers 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The error % between the PSO predicted result and the experimental result showed that PSO is an effective method to achieve the required objective. 42 GA is used to predict the optimum squeeze casting process parameters on TS, hardness and surface roughness. To convert the objective functions to single objective, different weights are provided to each objective.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The process starts with a 3D model, which is sliced by applying slicing algorithms with defined process parameters. [22][23][24] AM is a material-oriented manufacturing technology that has encouraged the minimal usage of material and energy. 25 AM has manifested several benefits -optimized material and energy usage, short supply chains, freeform design, optimized and light weight design, shape consolidation, multi-material processing, and minimal postprinting requirements.…”
Section: Introductionmentioning
confidence: 99%